2020
DOI: 10.3390/su12114428
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management in German Hospitals—A Classification of Approaches

Abstract: This paper analyzes organizational environmental performance and environmental management approaches in German hospitals. Based on data from an online survey and a subsequent cluster analysis, three groups of hospitals are identified: traditionalists, pragmatists, and environmentalists. The clusters differ regarding their organizational environmental performance, i.e., the environmental management elements adopted (policy, goals, structures, processes, and monitoring) and the environmental issues addressed (en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 80 publications
3
10
1
Order By: Relevance
“…The adoption of environmental strategies depends on internal as well as external forces in the political and economic contexts in which the firm operates, including the internal as well as external stakeholders [24] (p. 22). The Banerjee model identified four factors which have an impact on corporate environmentalism: public concern, regulatory pressure, competitive advantage and top management commitment.…”
Section: Factors Affecting Corporate Environmentalismmentioning
confidence: 99%
See 4 more Smart Citations
“…The adoption of environmental strategies depends on internal as well as external forces in the political and economic contexts in which the firm operates, including the internal as well as external stakeholders [24] (p. 22). The Banerjee model identified four factors which have an impact on corporate environmentalism: public concern, regulatory pressure, competitive advantage and top management commitment.…”
Section: Factors Affecting Corporate Environmentalismmentioning
confidence: 99%
“…Pedersen and Neergaard [33] argued that the green consumer is a rare and exclusive demographic. Seifert, Damert and Guenther [24], while studying the impact of hospital clients on the environmental management system of German hospitals, found customers as irrelevant stakeholders, and Zhang et al [34] found customers' pressures as an insignificant predictor of firms adopting intentions to green innovation in China. In addition, according to Raiz et al [35], customer priorities and their environmental guidelines are very different in emerging markets.…”
Section: Customer Concern and Corporate Environmentalismmentioning
confidence: 99%
See 3 more Smart Citations